PELAKSANAAN LATIHAN TANGGA NADA DAN INTERVAL DENGAN METODE DRILL PADA EKSTRAKURIKULER PADUAN SUARA (UNISONO) DI SMP NEGERI 16 PADANG - Irma Yeni; Yensharti (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of scale and interval exercises using a drill method during the choir extracurricular activities at SMP Negeri 16 Padang. Studying employs a qualitative approach with a descriptive method. Research informants consisted of the choir extracurricular instructor (as the primary informant) and five students (as supporting informants) selected through purposive sampling. Data was collected via observation, interviews, and documentation. The results indicate that the scale and interval exercises were conducted systematically, comprising planning, implementation, and evaluation stages. The exercises were carried out in a gradual and repetitive manner before being applied to the song